2021
DOI: 10.1016/j.jiac.2020.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Recent acute reduction in macrolide-resistant Mycoplasma pneumoniae infections among Japanese children

Abstract: Introduction: Mycoplasma pneumoniae contributes to numerous pneumonia cases among children and young adults. Therefore, this study aimed to investigate the prevalence of M. pneumoniae infections among Japanese children, occurring since 2008. Methods: Nasopharyngeal swab specimens were obtained from all cases, following which real-time PCR was performed to identify M. pneumoniae. Further, the p1 genotypes of isolates were determined using the PCR restriction fragment length polymorphism typing method. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 27 publications
3
21
1
1
Order By: Relevance
“…In our study, because of the widespread and routine use of testing for M. pneumoniae infections in our institution and affiliated urgent care centers, we were able to include a larger sample size of nonselected patients. The resistance mutations detected in our population are similar to others reported worldwide and confirmed that the A2063G mutation was the most commonly found ( 8 , 10 , 16 , 25 , 26 ). Although it is a novel mutation, a deletion on A2065Δ was detected in 3 isolates, but it did not confer phenotypic resistance to macrolides.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, because of the widespread and routine use of testing for M. pneumoniae infections in our institution and affiliated urgent care centers, we were able to include a larger sample size of nonselected patients. The resistance mutations detected in our population are similar to others reported worldwide and confirmed that the A2063G mutation was the most commonly found ( 8 , 10 , 16 , 25 , 26 ). Although it is a novel mutation, a deletion on A2065Δ was detected in 3 isolates, but it did not confer phenotypic resistance to macrolides.…”
Section: Discussionsupporting
confidence: 90%
“…Although epidemiological studies on M. pneumoniae infection have indicated that epidemics usually occur [11,12], infection incidence in Europe and Asia significantly increased in 2011-2012, 2015, and 2017 [2,9,11,[13][14][15]. Our study retrospectively analyzed the impact of the public health response to COVID-19 on the occurrence of M. pneumoniae infection among children in western China, based on analysis of data from 2017 to 2020.…”
Section: Discussionmentioning
confidence: 99%
“…In Korea, approximately 60–87% of children have the A2063G mutant [ 10 , 13 , 20 ]. The prevalence of macrolide-resistant M. pneumoniae was reportedly 87% in Japan during 2011 [ 21 ], although other Japanese groups had reported that the prevalence of macrolide-resistant M. pneumoniae has decreased recently in Japan [ 22 ]. In contrast, Korea and China have reported high proportions of macrolide-resistant M. pneumoniae infections until recently [ 12 , 23 ].…”
Section: Discussionmentioning
confidence: 99%